Exploring Periodic Bicontinuous Cubic Network Structures with Complete Phononic Bandgaps - Hur, Kahyun; Hennig, Richard G.; Wiesner, Ulrich (American Chemical Society, 2017)
Controlling the phononic properties of materials provides opportunities for better thermal insulation, reduction of sound noise, and conversion of wasted heat into electricity. Phononic crystals are periodically structured media composed of two or more dissimilar materials offering a unique pathway to control the transmission of phonons, responsible for sound and heat transport. In particular, phononic crystals with cubic network structure possessing complete phononic bandgaps are highly desirable for energy applications but have not been thoroughly investigated, hampering progress in this field. Here we computationally obtained phononic band structures of 16 cubic network structures that could be made by fabrication techniques including block copolymer self-assembly and identified six structures that exhibit complete phononic bandgaps. The champion phononic bandgap structure is the so-called I-WP structure with a bandgap width of 0.41. On the basis of simulation results, design rules to tailor network structures for larger phononic bandgaps are elucidated. We expect that our results will provide guidance to develop novel materials for sonic and thermal devices.
Keywords: MINIMAL-SURFACES; BLOCK-COPOLYMERS; ELASTIC-WAVES